Spatiotemporal Variability in Transport and Reactive Processes Across a First‐ to Fifth‐Order Fluvial Network. Issue 5 (23rd May 2020) - Gootman, Kaylyn S.; González‐Pinzón, Ricardo; Knapp, Julia L. A.; Garayburu‐Caruso, Vanessa; Cable, Jaye E.
Abstract: Fluvial networks integrate, transform, and transport constituents from terrestrial and aquatic ecosystems. To date, most research on water quality dynamics has focused on process understanding at individual streams, and, as a result, there is a lack of studies analyzing how physical and biogeochemical drivers scale across fluvial networks. We performed tracer tests in five stream orders of the Jemez River continuum in New Mexico, USA, to quantify reach‐scale hyporheic exchange during two different seasonal periods to address the following: How do hyporheic zone contributions to overall riverine processing change with space and time? And does the spatiotemporal variability of hyporheic exchange scale across fluvial networks? Combining conservative (i.e., bromide) and reactive (i.e., resazurin) tracer analyses with solute transport modeling, we found a dominance of reaction‐limited transport conditions and a decrease of the contributions of hyporheic processing across stream orders and flow regimes. Our field‐based findings suggest that achieving knowledge transferability of hyporheic processing within fluvial networks may be possible, especially when process variability is sampled across multiple stream orders and flow regimes. Therefore, we propose a shift in our traditional approach to investigating scaling patterns in transport processes, which currently relies on the interpretation of studies conducted in multiple sites (mainly in headwater streams) that are located in different fluvial networks, to a more cohesive, network‐centered investigation of processes using the same or readily comparable methods. Key Points: Reactive tracer tests revealed reaction‐limited conditions along a first‐ to fifth‐order fluvial network during contrasting flow regimes Processing rate coefficients and Damköhler numbers decreased along the continuum Results support modeling expectations of decreasing hyporheic contributions along fluvial networks